KESADARAN TRANSENDENTAL SEBAGAI PILAR UTAMA PENDIDIKAN BERWATAK DALAM UNTAIAN NASEHAT LUQMAN AL HAKIM - Hikami, Muhammad Waston Al (IAIN Salatiga, 2009)
Luqman the Wise, one of man who is mentioned in the Holy Qur`an, is not a prophet neither messenger of God. He is just an ordinary man like us. What differing between us and him is the noble idea of this man regarding the way he educates his children. Luqman educated his children by planting the consciousness of God in the heart of his children. By this awareness, children will raise not only with strong intellectual ability but also beautiful manners, respecting values of humanities and coloring their live with high values of moralities. This article explores Luqman wise words that were recorded in Surah Luqman verses 13 until 19 and evaluates the key success of Luqman’s education system. Compared to modern concept of character education, Luqman method was in accordance with its spirit and goal. Furthermore, the writer found that the core value which is always exists and building all Luqman’s wise words is the consciousness of the existence of God. In Islamic perspective, this transcendental awareness is the basic value for all process of character building in creating good habituation and manner known as akhlaaq al kariimah.